Fracture Behavior and Integrity of Different Direct Restorative Materials to Restore Noncarious Cervical Lesions - Battancs Emese; Fráter Márk; Sáry Tekla; Gál Emese; Braunitzer Gábor; Szabó Balázs P; Garoushi Sufyan (United Kingdom, 2022)
The purpose of this study was to analyze the fracture resistance and marginal leakage of noncarious cervical lesion (NCCL) restorations made of different restorative materials. Eighty upper premolars were randomly divided into four groups (n = 20/group). Standardized NCCL cavity preparations were performed on the buccal surface of the teeth and then restored with four different materials. Group 1: Packable resin composite (PC); Group 2: Highly flowable resin composite (HF); Group 3: Low flowable resin composite (LF); Group 4: Resin modified glass ionomer cement (RMGIC). After restorations were completed, cyclic and static fracture behavior was evaluated using a loading testing machine. Extra restored teeth were sectioned and then stained (n = 5/group). The specimens were viewed under a stereo microscope and the percentage of microgaps at the tooth-restoration interface was calculated. All restored teeth survived after fatigue loading. There was no statistically significant (p > 0.05) difference between the tested restorations after the static loading test. NCCLs restored with highly filled flowable composite showed the least microleakage among the tested groups (p < 0.05). The investigated restorative materials are acceptable for NCCL restorations in terms of fracture resistance and microleakage.